Inflammatory Kinetics and Efficacy of Anti-inflammatory Treatments on Human Nucleus Pulposus Cells. Issue 13 (1st July 2015) - Walter, Benjamin A.; Purmessur, Devina; Likhitpanichkul, Morakot; Weinberg, Alan; Cho, Samuel K.; Qureshi, Sheeraz A.; Hecht, Andrew C.; Iatridis, James C.
<x xml:space="preserve">Abstract</x> Study Design. Human nucleus pulposus (NP) cell culture study investigating response to tumor necrosis factor-α (TNFα), effectiveness of clinically available anti-inflammatory drugs, and interactions between proinflammatory cytokines. Objective. To characterize the kinetic response of proinflammatory cytokines released by human NP cells to TNFα stimulation and the effectiveness of multiple anti-inflammatories with 3 substudies: Timecourse, Same-time blocking, Delayed blocking. Summary of Background Data. Chronic inflammation is a key component of painful intervertebral disc degeneration. Improved efficacy of anti-inflammatories requires better understanding of how quickly NP cells produce proinflammatory cytokines and which proinflammatory mediators are most therapeutically advantageous to target. Methods. Degenerated human NP cells (n = 10) were cultured in alginate with or without TNFα (10 ng/mL). Cells were incubated with 1 of 4 anti-inflammatories (anti-IL-6 receptor/atlizumab, IL-1 receptor anatagonist, anti-TNFα/infliximab and sodium pentosan polysulfate/PPS) in 2 blocking-studies designed to determine how intervention timing influences drug efficacy. Cell viability, protein, and gene expression for IL-1β, IL-6, and IL-8 were assessed. Results. Timecourse: TNFα substantially increased the amount of IL-6, IL-8, and IL-1β, with IL-1β and IL-8 reaching equilibrium within ∼72 hours (IL-1β: 111 ± 40 pg/mL, IL-8: 8478 ± 957 pg/mL), and IL-6 not reaching steady state after 144 hours (1570 ± 435 pg/mL). Anti-TNFα treatment was most effective at reducing the expression of all cytokines measured when added at the same time as TNFα stimulation. Similar trends were observed when drugs were added 72 hours after TNFα stimulation, however, no anti-inflammatories significantly reduced cytokine levels compared with TNF control. Conclusion. IL-1β, IL-6, and IL-8 were expressed at different rates and magnitudes suggesting different roles for these cytokines in disease. Autocrine signaling of IL-6 or IL-1β did not contribute to the expression of any proinflammatory cytokines measured in this study. Anti-inflammatory treatments were most effective when applied early in the inflammatory process, when targeting the source of the inflammation. Level of Evidence: N/A